2016
DOI: 10.1016/j.ccell.2016.08.016
|View full text |Cite|
|
Sign up to set email alerts
|

Glycerophosphodiesterase GDE2 Promotes Neuroblastoma Differentiation through Glypican Release and Is a Marker of Clinical Outcome

Abstract: Neuroblastoma is a pediatric embryonal malignancy characterized by impaired neuronal differentiation. A better understanding of neuroblastoma differentiation is essential for developing new therapeutic approaches. GDE2 (encoded by GDPD5) is a six-transmembrane-domain glycerophosphodiesterase that promotes embryonic neurogenesis. We find that high GDPD5 expression is strongly associated with favorable outcome in neuroblastoma. GDE2 induces differentiation of neuroblastoma cells, suppresses cell motility, and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 57 publications
4
91
0
Order By: Relevance
“…This implies that GDE2 enzymatic regulation of specific GPI-anchored proteins is central to its function in neuronal survival. We conducted a proteomic screen to identify GPI-anchored substrates of GDE2 and found Glypican 4 and 6, both of which have been reported as GDE2 substrates [9, 13]. We then demonstrated that the non-membrane versions of these proteins, as well as Glypican 1, are reduced in SOD1 G93A mice.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This implies that GDE2 enzymatic regulation of specific GPI-anchored proteins is central to its function in neuronal survival. We conducted a proteomic screen to identify GPI-anchored substrates of GDE2 and found Glypican 4 and 6, both of which have been reported as GDE2 substrates [9, 13]. We then demonstrated that the non-membrane versions of these proteins, as well as Glypican 1, are reduced in SOD1 G93A mice.…”
Section: Discussionmentioning
confidence: 94%
“…Protein complexes that yielded more signal in the WT, indicative of impaired GPI-anchor cleavage in the Gde2 KO, were then identified using mass spectrometry. This screen identified two members of the Glypican family of heparin sulfate proteoglycans, Glypican 6 and Glypican 4, and both of these GPI-anchored proteins have been reported as substrates of GDE2 [9, 13]. We hypothesized that if the production of non-membrane bound Glypican 4 and Glypican 6 via GPI-anchor cleavage was crucial to prevent degeneration, we should see diminished production of these proteins in mouse models that exhibit motor neuron degeneration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We specifically used the following datasets: Neuroblastoma Ghent (Array Express: E-MTAB-2618) [19] and Neuroblastoma SEQC (GEO: GSE62564). Kaplan Mier curves were obtained through R2 as described by Matas-Rico E et al [35]. …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, another study has shown that neuroblastoma differentiation is promoted by release of a GPI-anchored HSPG, Glypican-6 (GPC6) through via Glycerophosphodiesterase (GDE2). This study also found that high GDE2 or low GPC6 level in neuroblastoma predicted significantly increased patient survival (108). These studies are of high significance as they make two major points; first, that the differentiation state of the cancer cells predict survival, and second, that HS and HSPGs are among the key regulators of cancer differentiation states.…”
Section: Cell-autonomous Role Of Hs and Hspgs In Cancer Initiation Anmentioning
confidence: 64%